PENGARUH KETERAMPILAN LITERASI INFORMASI PUSTAKAWAN TERHADAP KUALITAS KOLEKSI PERPUSTAKAAN PERGURUAN TINGGI NEGERI KALIMANTAN SELATAN - Laila Rahmawati; Siti Wahdah; Juairiah (Jurnal Komunikasi, 2024)
Librarians with a background in library science must have expertise in using, understanding, searching, and evaluating information. This information literacy skill is the main expertise of librarians who have an impact on the information in the library, especially the college library. Good librarian information literacy skills can ultimately present information that suits the needs of users. Not only that, the quality of the information is also presented accurately. This study aims to determine the correlation of information literacy skills of librarians with the collection quality of state university libraries in South Kalimantan. The research method used is quantitative with regression analysis. All librarians at state universities totaling 51 people with saturated sampling technique. Based on the table results Paired Samples Correlations obtained Correlation=0,236 with value P atau sig=0,061. So the correlation value is very strong because the approach to 1, so that it can be stated that there is a correlation between information literacy skills and collection quality in the South Kalimantan state university library